2014
DOI: 10.1155/2014/862969
|View full text |Cite
|
Sign up to set email alerts
|

Drug Retention Rates and Treatment Discontinuation among Anti-TNF-αAgents in Psoriatic Arthritis and Ankylosing Spondylitis in Clinical Practice

Abstract: Objective. The study aim was to determine treatment persistence rates and to identify causes of discontinuation in psoriatic arthritis (PsA) and ankylosing spondylitis (AS) patients in clinical practice. Methods. Patients treated with adalimumab (ADA), etanercept (ETA), or infliximab (INF) were retrospectively included. Treatment persistence rates were analyzed by means of a stepwise logistic regression. Differences between therapy duration were assessed by means of an analysis of variance model (ANOVA), while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 42 publications
6
41
2
2
Order By: Relevance
“…TNFi-iv. In the findings reported here, the discontinuation rate (31%) was similar to the discontinuation rate (34%) in a previous study of TNFis in patients with AS [23]; however, the rate of switching to a new TNFi (21%) fell between the results of previous studies (4-30%) [23,24,32]. Previous studies have confirmed that while switching to a second TNFi can be effective in AS, overall effectiveness may be somewhat lower [21,33,34].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…TNFi-iv. In the findings reported here, the discontinuation rate (31%) was similar to the discontinuation rate (34%) in a previous study of TNFis in patients with AS [23]; however, the rate of switching to a new TNFi (21%) fell between the results of previous studies (4-30%) [23,24,32]. Previous studies have confirmed that while switching to a second TNFi can be effective in AS, overall effectiveness may be somewhat lower [21,33,34].…”
Section: Discussionsupporting
confidence: 84%
“…The percentage of patients in this study who discontinued or switched TNFis (59.4%) was higher than in the previous studies [22][23][24]32]. Although the current study did not evaluate the reasons patients switched or discontinued TNFi therapy, previous studies have shown that approximately 30-36% of patients with AS, discontinued or switched biologic therapy because of adverse events [35,36] or lack of treatment effect [37].…”
Section: Add-on Medication N (%)contrasting
confidence: 56%
“…For example, biologics registries have provided invaluable data about treatment switching and long-term drug retention rates, which reflects efficacy, safety and adherence to the drug [28][29][30]. They helped elucidate the very debated association between biologics and malignancies and provided solid reassurance about this major safety issue [31][32].…”
Section: Registries In Rheumatic Diseasesmentioning
confidence: 99%
“…Так, в исследовании с участием 268 пациентов с ревматическими заболеваниями анализ причин отмены иФНОα показал, что частота пре-кращения лечения из-за появления НР значимо не различа-ется у препаратов этой группы [14]. Наиболее частыми НР были инфузионные реакции, инфекции, печеночная, по-чечная или гематологическая дисфункции, сердечно-сосу-дистые, неврологические и психотические нарушения, зло-качественные новообразования.…”
Section: безопасность гибп: значение рекомендаций Eular-2013unclassified